Original Research: miR-194 inhibits proliferation and invasion and promotes apoptosis by targeting KDM5B in esophageal squamous cell carcinoma cells - Cui, Guanghui (Exp Biol Med (Maywood), 2016)
Increasing evidence suggests that miR-194 is down-regulated in esophageal squamous cell carcinoma tumor tissue. However, the role and underlying mechanism of miR-194 in esophageal squamous cell carcinoma have not been well defined. We used DIANA, TargetScan and miRanda to perform target prediction analysis and found KDM5B is a potential target of miR-194. Based on these findings, we speculated that miR-194 might play a role in esophageal squamous cell carcinoma development and progression by regulation the expression of KDM5B. We detected the expression of miR-194 and KDM5B by quantitative real-time reverse transcription PCR (qRT-PCR) and Western blot assays, respectively, and found down-regulation of miR-194 and up-regulation of KDM5B existed in esophageal squamous cell carcinoma cell lines. By detecting proliferation, invasion and apoptosis of TE6 and TE14 cells transfected with miR-194 mimics or mimic control, miR-194 was found to inhibit proliferation and invasion and promote apoptosis of esophageal squamous cell carcinoma cells. miR-194 was further verified to regulate proliferation, apoptosis and invasion of esophageal squamous cell carcinoma cells by directly targeting KDM5B. Furthermore, animal studies were performed and showed that overexpression of miR-194 inhibited the growth of esophageal squamous cell carcinoma tumors in vivo. These results confirmed our speculation that miR-194 targets KDM5B to inhibit esophageal squamous cell carcinoma development and progression. These findings offer new clues for esophageal squamous cell carcinoma development and progression and novel potential therapeutic targets for esophageal squamous cell carcinoma.